2015
DOI: 10.1007/s10439-015-1381-9
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Specific Surgical Planning, Where Do We Stand? The Example of the Fontan Procedure

Abstract: The Fontan surgery for single ventricle heart defects is a typical example of a clinical intervention in which patient-specific computational modeling can improve patient outcome: with the functional heterogeneity of the presenting patients, which precludes generic solutions, and the clear influence of the surgically-created Fontan connection on hemodynamics, it is acknowledged that individualized computational optimization of the post-operative hemodynamics can be of clinical value. A large body of literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 43 publications
0
29
0
1
Order By: Relevance
“…This study shows that APC flow significantly affects the TCPC hemodynamics and demonstrates that it is possible to include the effect of such APC flow on the TCPC flow distribution during patient‐specific CFD simulations. A recent review of the field of patient‐specific simulation of the Fontan circulation concluded by highlighting the need for validation of predictive capabilities (de Zélicourt & Kurtcuoglu, ). Our contribution to this endeavour is preliminary findings in two patients, showing that the effect of surgical and catheter interventions can be predicted using the proposed CFD analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This study shows that APC flow significantly affects the TCPC hemodynamics and demonstrates that it is possible to include the effect of such APC flow on the TCPC flow distribution during patient‐specific CFD simulations. A recent review of the field of patient‐specific simulation of the Fontan circulation concluded by highlighting the need for validation of predictive capabilities (de Zélicourt & Kurtcuoglu, ). Our contribution to this endeavour is preliminary findings in two patients, showing that the effect of surgical and catheter interventions can be predicted using the proposed CFD analysis.…”
Section: Discussionmentioning
confidence: 99%
“…1 Unequal distribution of hepatic blood flow, which may result from suboptimal total caval pulmonary connection geometry, is an identified mechanism for the development of PAVMs. 2 In the current issue of the Journal, Trusty and colleagues 3 used Fontan surgical planning to evaluate preoperative and postoperative hemodynamics among 12 patients with single ventricles (5 Fontan revisions, 7 Fontan completions). Fontan surgical planning uses flow simulation models to predict post-Fontan hemodynamics in an effort to improve hepatic flow distribution (HFD).…”
Section: Travis J Wilder MDmentioning
confidence: 99%
“…In single ventricle lesions, especially at the Fontan stage, numerical simulations have been used to understand patient hemodynamics (Khiabani et al, 2015; Marsden et al, 2007; Tang et al, 2014), test novel treatment concepts (Esmaily-Moghadam et al, 2015; Trusty et al, 2016; Yang et al, 2013), and predict surgical outcomes (de Zélicourt et al, 2011; de Zélicourt and Kurtcuoglu, 2015; Haggerty et al, 2012; Kung et al, 2013; Sundareswaran et al, 2009a). Cardiovascular simulation has become a fruitful area of translational research and has potential to impact clinical decisions, especially by assisting surgical planning (de Zélicourt and Kurtcuoglu, 2015; Fogel et al, 2013; Marsden and Esmaily-Moghadam, 2015; Marsden, 2014; Restrepo et al, 2015b). Figure 1 illustrates a standard procedure of the surgical planning for congenital single ventricle heart diseases.…”
Section: Introductionmentioning
confidence: 99%
“…However, these previous studies rely on small sample sizes limiting their ability to comprehensively understand the sensitivity of using time-averaged BCs on Fontan simulations at a population level. In addition, most of the previously mentioned studies focus on Fontan energetics and only marginally discussed hepatic flow distribution, which some argue is a more important Fontan hemodynamic metric for current clinical practice (de Zélicourt and Kurtcuoglu, 2015; Pike et al, 2004; Srivastava et al, 1995; Sundareswaran et al, 2009a; Yang et al, 2013). …”
Section: Introductionmentioning
confidence: 99%